Analisis Karakteristik Gaya Belajar Vak (Visual, Auditorial, Kinestetik) Siswa Kelas X SMAK St. Petrus Ende Tahun Ajaran 2019/2020 - Norbertus Labu (Jurnal Penelitian Pendidikan Agama Katolik, 2021)
This research aims to describe the characteristics of the VAK (visual, auditory, kinesthetic) learning styles of students or learners. Learning style is a very important learning modality. Information relating to the characteristics of student learning styles is very important for the teacher so that the teacher can choose a fixed learning strategy, which will thus improve the quality of learning. Students will also more easily motivate themselves in learning. This research is non-experimental and classified as a qualitative analytical descriptive study. The subjects of this research were all students of class X SMAK St. Petrus Ende 2019/2020 school year. The instrument used in this research was a questionnaire filled out by research subjects. This learning style questionnaire was filled out by 189 students of class X of SMAK St. Petrus Ende 2019/2020 school year. The results of the analysis of the learning styles of class Xa students are dominated by auditory learning styles (50.00%). Class Xb is dominated by auditory learning styles (60.53%). Class Xc is dominated by auditory learning styles (68.42%). Class Xd is dominated by a combined visual and auditory learning style (37.84%). Class Xe is dominated by auditory learning styles (55.27%). Overall learning styles of class X students of SMAK St. Petrus Ende class of 2019/2020 is dominated by auditory learning style that is equal to 52.91%.